2011
DOI: 10.1002/jrs.2722
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and structural investigations of α‐, β‐, and γ‐AlH3 phases

Abstract: With its reputation as a high-energy density fuel, aluminum hydride (AlH 3 ) has received renewed attention as a material that is particularly suitable, not only for hydrogen storage but also for rocket propulsion. While the various phases of AlH 3 have been investigated theoretically, there is a shortage of experimental studies corroborating the theoretical findings. In response to this, we present here an investigation of these compounds based primarily on two research areas in which there is the greatest sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…A more recent DTF study by Vajeeston et al [64] demonstrated different frequencies for the vibration modes of α-AlH 3 , which is shown in Table 2 . Manciu et al [65] analyzed the Raman absorption of asprepared α-AlH 3 synthesized by wet chemical method and showed two vibrations at 508 cm −1 and 720 cm −1 ( Table 2 ), which is very similar to those reported by Wong and Miller [61] and by Tkacz et al [66] .…”
Section: Spectroscopic Studysupporting
confidence: 77%
“…A more recent DTF study by Vajeeston et al [64] demonstrated different frequencies for the vibration modes of α-AlH 3 , which is shown in Table 2 . Manciu et al [65] analyzed the Raman absorption of asprepared α-AlH 3 synthesized by wet chemical method and showed two vibrations at 508 cm −1 and 720 cm −1 ( Table 2 ), which is very similar to those reported by Wong and Miller [61] and by Tkacz et al [66] .…”
Section: Spectroscopic Studysupporting
confidence: 77%
“…Figures 9b and 9c show the Al-H stretching bands at 1857 and 1725 cm −1 and Al-H bending bands at lower frequencies (874, 740, and 673 cm −1 ) that are attributed to α-AlH 3 . The IR spectra of the washed samples match that of pure α-AlH 3 and correspond well with IR spectroscopic data described in the literature [23,24].…”
Section: Xrd and Ftir Characterizationsupporting
confidence: 52%
“…Using X-ray and neutron diffraction as well as spectroscopic techniques, the crystal and electronic structures for four phases (a, a 0 , b and g) have been characterized for AlH 3 (or AlD 3 ). [79][80][81][82][83][84][85][86][87] As the most stable phase, a-AlH 3 has a trigonal structure (space group R% 3c) with corner sharing of the [AlH 6 ] octahedra ( Fig. 1e, 10).…”
Section: Alhmentioning
confidence: 99%